Comparing the Result of Infrastructure and Facility Demand Distribution Similarity Test Between Using Percentage Value and Real Value - Hitapriya Suprayitno; Vita Ratnasari; Ria Asih Aryani Soemitro (Journal of Infrastructure & Facility Asset Management, 2020)
Understanding the Infrastructure & Facility Demand Behaviour is important. Sometimes, comparing two Demand Behaviour need to be done. A method to make Distribution Similarity test has been developed for Transportation Trip Length Distribution Similarity test. This test can be used for comparing Infrastructure & Facility Demand Behavior. There are still questions on whether the test must be made upon the Distribution of Real Value or upon the Distribution of Percentage Value. The research result indicates that Comparing Distribution Similarity must use Distribution Percentage Value. The similarity must be measured based on Accepted Goodness of Fit measured in χ2 Value, and Accepted Difference Value measured in Absolute Difference Value.